STUDI TATA RIAS DAN BUSANA PENGANTIN LEGHA SUMENEP MADURA - sulis, Sulistiami; Nuraini, Iut (LPPM Universitas PGRI Adi Buana Surabaya, 2017)
Marriage isthe most sacred ceremony in the course of human life,each region hasits own proceduresperformed by tribes Madura in general and especially in the city Sumenep. Make up and bridalfashion become the center ofattention of the public and guests who attended the wedding,therefore,the bride would want to look attractive. Bridal Sumenep on each night receptionis dividedinto three kinds, namely legha bridal make up, bridal make up bridal make up kapotren and candles.The discussion on this matter is devoted to review of bridal legha. This research is motivated by thefact that Indonesia is actually rich variety harmoninasi customs in public life. The procedure foreachevent must be different tribe, one of the brides in East Java there that has a characteristicunique make up, among others Madura particularly Sumenep. Formulation of the problem in thisstudy is